An analysis of PEM water electrolysis cells operating at elevated current densities. (19th April 2019) - Villagra, A.; Millet, P.
Abstract: Recent developments related to the operation of PEM water electrolysis cells at elevated current density are reported. First, a cost analysis has been performed to discuss the interest of extending the range of operating current density of these cells, towards the 10 A cm −2 range and above. Then the technical impact this may have on the cell design has been analyzed, and the practical conditions required to remove the extra-heat and to facilitate fluid transport across the porous transport layers have been identified. Experimental current-voltage polarization curves have been measured using a pressurized laboratory cells equipped with PFSA (perfluoro-sulfonic acid) membranes of various thicknesses, operating at 80 °C and current densities up to 10 A cm −2 . These experimental polarization curves have been fitted using model equations. Key cell parameters such as internal cell resistance, charge transfer exchange current densities and roughness factors have been determined from these fits. The impact of the cell design on the performance and efficiency of PEM water electrolysis cells operated in the multi A cm −2 range of current density has been analyzed, with a focus on the situation that prevails above 5 A cm −2 . Highlights: The impact of large current densities on water electrolysis cells is analyzed. Polarization curves up to 10 A cm −2 are reported. A model is used to determine microscopic rate parameters. Guidelines for future developments are provided.